Analisis Perilaku Biaya Mahasiswa (Studi Kasus Pada Mahasiswa Akuntansi Universitas Mataram) - Perwangsa, Baiq Hera Yulanda; Fikri, M. Ali; Suryantara , Adithya Bayu (Fakultas Ekonomi dan Bisnis Unram, 2025)
The purpose of this study is to analyze the allocation of costs spent by a student for his needs through an accounting perspective. The benefit of this study is so that each individual can overcome life problems, which are mostly related to material or resources. When individuals are faced with various offers from the surrounding environment, they must be able to react by determining the profit and loss through cost analysis in order to survive. This study uses a questionnaire method in collecting data and grouping it into two parts, namely early semester students (1-6) and final semester students (7>, or students who are writing their thesis). The results of the analysis of the cost grouping can be seen that the cost behavior incurred by group I is the same as the general cost behavior (namely other costs, tuition fees, and entertainment costs), except for the final semester group 7> (group II), namely the cost behavior is somewhat different, where they tend to spend more entertainment money than tuition fees.